Wyprysk kontaktowy - Śpiewak, Radosław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Contact eczema is one of the most common clinical pictures seen in general practice. This is not a defined disease, but rather an umbrella term for a group of diseases with various aetiology that share common features in the clinical picture and course of the disease. The term itself implies that the causative factor provokes disease through direct contact with the skin. The following diseases fit into the spectrum of contact eczema: 1) Allergic contact eczema (allergic contact dermatitis), in which a low-molecular weight chemical compound (hapten) penetrates into the skin, and binds to an autologous protein to form an antigen that can be processed and recognized by cells of the immune system. Hapten-specific hypersensitivity of an individual is a prerequisite for this reaction. The orchestrators and major players in allergic contact eczema are effector T lymphocytes. 2) Irritant contact dermatitis (toxic dermatitis), in which the cumulative damage by various irritant factors leads to initiation of the inflammatory reaction and disruption of the skin barrier. The majority of people chronically exposed to irritants will eventually develop the disease. Individual susceptibility of the exposed person may play a role in the case of weak irritants, whereas most people will react with eczema upon exposure to strong irritants. 3) Protein contact dermatitis (also referred to as “atopic contact eczema”), in which an inflammatory reaction of the skin is provoked by contact with large molecular weight proteins (full allergens, in contrast to haptens in ACD). Typically, this form of contact eczema is seen in atopic individuals handling proteins (chefs, sandwich makers, etc.). Protein contact dermatitis is related to immunological contact urticaria, which can precede, accompany or replace eczema. Whichever disease of this spectrum is suspected, all others must be included in the differential diagnosis. Moreover, co-existence of these diseases is not rare.